Extragingival pyogenic granuloma - Anita Munde; Pranali Wankhede; Jitendra Kalburge; Safia Shoeb; Sunil Sahuji (Wolters Kluwer Medknow Publications, 2011)
The pyogenic granuloma is thought to represent an exuberant tissue response to local irritation or trauma. Clinically, these lesions usually present as single nodule or sessile papule with smooth or lobulated surface. Although it is known to show a striking predilection for the gingiva (75% of all cases), it can be found extragingivally with varying clinical features that sometimes may mimic more serious lesions, such as malignancies. The clinical diagnosis of such an uncommon extragingival pyogenic granuloma can be quite challenging. The purpose of this article is to report an unusual case of extragingival pyogenic granuloma occurring on the dorsal surface of tongue.